Abanfan matilon, a local wisdom in marine ethnoconservation system on the coast of Liki Island, Sarmi District, Papua, Indonesia - HENDERINA JOSEFINA KEILUHU; PUGUH SUJARTA; SUHARNO SUHARNO; MARZELINE G. MAILISSA; SUWARNO HADISUSANTO; SARAH YULIANA; AHMAD DWI SETYAWAN (Society for Indonesian Biodiversity, 2023)
Abstract. Keiluhu HJ, Sujarta P, Suharno, Mailissa MG, Hadisusanto S, Yuliana S, Setyawan AD. 2023. Abanfan matilon, a local wisdom in marine ethnoconservation system on the coast of Liki Island, Sarmi District, Papua, Indonesia. Biodiversitas 24: 4693-4701. Liki Island is the outermost part of Sarmi District, Papua, Indonesia, which is directly facing the Pacific Ocean and bordering Papua New Guinea. This island is unique in its geographical features and is characterized by the local wisdom of the people known as Abanfan matilon. Therefore, this study aimed to document the knowledge, participation of people, and the role of the local wisdom of Abanfan matilon in the marine ethnoconservation system. The study was conducted from June to November 2022 using a survey method based on semi-structural interviews. The results of the study of 50 respondents showed that (i) the community knowledge about local wisdom of Abanfan matilon, possed by the Liki Island village community, had transcended from one generation to another through oral stories from parents, (ii) the role of the community in implementing local wisdom was substantial, starting from the planning, preparation, and implementation up to the harvesting activities through local traditional ceremonies, and (iii) the implementation of local wisdom of Abanfan matilon was carried out by community leaders from various sectors, including traditional, church, or local government. In conclusion, local wisdom traditions in Abanfan matilon exhibited the characteristics of a marine ethnoconservation system.